2021
DOI: 10.5194/acp-21-731-2021
|View full text |Cite
|
Sign up to set email alerts
|

Slow feedbacks resulting from strongly enhanced atmospheric methane mixing ratios in a chemistry–climate model with mixed-layer ocean

Abstract: Abstract. In a previous study the quasi-instantaneous chemical impacts (rapid adjustments) of strongly enhanced methane (CH4) mixing ratios have been analysed. However, to quantify the influence of the respective slow climate feedbacks on the chemical composition it is necessary to include the radiation-driven temperature feedback. Therefore, we perform sensitivity simulations with doubled and quintupled present-day (year 2010) CH4 mixing ratios with the chemistry–climate model EMAC (European Centre for Medium… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 67 publications
2
3
0
Order By: Relevance
“…Although regional effects might be affected by internal variability and are likely model-dependent, our results provide evidence that the representation of water vapor in the lowermost stratosphere in models has impacts in the troposphere, potentially shifting storm tracks and weather patterns, and causes uncertainties in simulating surface climate. The emergence of clear tropospheric impacts in our model experiment with constrained sea-surface temperatures (“Methods” section) is consistent with results from more idealized studies 3 , and the surface temperature response in fully coupled atmosphere-ocean models can be expected to be even larger 32 .…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Although regional effects might be affected by internal variability and are likely model-dependent, our results provide evidence that the representation of water vapor in the lowermost stratosphere in models has impacts in the troposphere, potentially shifting storm tracks and weather patterns, and causes uncertainties in simulating surface climate. The emergence of clear tropospheric impacts in our model experiment with constrained sea-surface temperatures (“Methods” section) is consistent with results from more idealized studies 3 , and the surface temperature response in fully coupled atmosphere-ocean models can be expected to be even larger 32 .…”
Section: Resultssupporting
confidence: 86%
“…The somewhat idealized model set-up used here, based on an atmospheric GCM and modifying only water vapor transport above 250 hPa, allows a clear separation of the radiation and circulation effects due to changes in lowermost stratospheric water vapor. It should be noted that the fixed SSTs suppress the slow climate feedbacks and that surface temperature changes will be even larger when including coupling to the ocean 32 . Hence, the presented near–surface impacts on circulation and temperature at 850 hPa can likely be interpreted as lower limits of the response to changes in lowermost stratospheric water vapor.…”
Section: Methodsmentioning
confidence: 99%
“…Although regional effects might be affected by internal variability and are likely model-dependent, our results provide evidence that the representation of water vapor in the lowermost stratosphere in models has impacts in the troposphere, potentially shifting storm tracks and weather patterns, and causes uncertainties in simulating surface climate. The emergence of clear tropospheric impacts in our model experiment with constrained sea-surface temperatures (Methods) is consistent with results from more idealized studies [3], and the surface temperature response in fully coupled atmosphere-ocean models can be expected to be even larger [32].…”
Section: Effects On Atmospheric Circulationsupporting
confidence: 86%
“…forest 4 , an enhanced hydrological cycle 12 and expansive shallow shelf seas 5,13 , in particular in the southern Tethys and Arctic oceans. Earlier studies also suggested a nonlinear increase in the lifetime of CH 4 due to weaker sinks when concentrations of CH 4 are increased from modern values 14,15 . Hence CH 4 concentrations are highly uncertain in deep time.…”
Section: Formation Of Polar Stratospheric Cloudsmentioning
confidence: 92%